Polyembryony ability of jackfruit (Artocarpus heterophyllus) seed - Muhamad, Nur Farah Dinah (2013)
Polyembryony is common in jackfruit but which part of the seed responded to polyembryony is the main issue. The development of multiple embryos within the same seed is defined as polyembryony. The objectives of the experiment were to compare the ability of different structural forms of seed and the effect of different concentration of benzylaminopurine (BAP) on shoot induction through polyembryony in Artocarpus heterophyllus seed while the different structural forms of seed tested were complete seed, seed without minor cotyledon and seed without minor cotyledon and zygotic embryo. The different concentrations of BAP were 0 mg/L, 4 mg/L and 8 mg/L. The experiment was arranged in a Randomized Complete Block Design (RCBD) with 9 treatments and 10 replications for each treatment. Each replication contained one explant. The different seed structures were cultured inside jars containing half strength MS (Murshige and Skoog) medium with different concentrations of BAP. After 12 weeks of culture, it was observed that complete seed cultured on medium supplemented with 4 mg/L BAP showed the best response producing the highest number and percentage of shoot induction.